2020
DOI: 10.1080/11038128.2020.1820570
|View full text |Cite
|
Sign up to set email alerts
|

Occupational performance goals and outcomes of time-related interventions for children with ADHD

Abstract: Background: Children with attention deficit hyperactivity disorder (ADHD) have difficulties with occupational performance, related to difficulties with time-processing ability. Aims: To examine the outcome of a multimodal time-related intervention designed to support children aged 9-15 years with ADHD, to achieve their occupational performance goals and improve satisfaction with occupational performance. A further aim was to compare the children's ratings of outcome with their parents' ratings and to analyse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
3
0
1
Order By: Relevance
“…Attention-deficit/hyperactivity disorder (ADHD) is one of the most common disorders in children. Children with ADHD often have problems in different areas of occupation (Sattari et al, 2015; Wennberg et al, 2021). Noting the need for client-centered interventions in children with ADHD in occupational therapy (Graham et al, 2009), it is necessary to use occupation-based outcomes to indicate health, wellbeing, and occupational participation at the individual level.…”
Section: Introductionmentioning
confidence: 99%
“…Attention-deficit/hyperactivity disorder (ADHD) is one of the most common disorders in children. Children with ADHD often have problems in different areas of occupation (Sattari et al, 2015; Wennberg et al, 2021). Noting the need for client-centered interventions in children with ADHD in occupational therapy (Graham et al, 2009), it is necessary to use occupation-based outcomes to indicate health, wellbeing, and occupational participation at the individual level.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, individuals with ADHD and ASD had later sleep onset during weekdays (around 30-45 min later in ADHD and ASD than in controls), and young people with ASD woke up earlier than controls despite a later sleep onset time [25]. Earlier studies on children with ADHD have also studied the importance of establishing morning and evening routines independently within set time, indicating a need for interventions targeting morning and evening routines [79]. Whether the improved evening and morning routine findings in the current study are due to differences in sleep patterns, reduced anxiety and/or improved sleep hygiene (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier findings suggest that methylphenidate has a specific effect on improving timing deficits in ADHD ( Smith et al, 2013 ). Recent studies have shown that cognitive training with time-related interventions, referred to as time-skills training, also improve everyday time management, facilitate the carrying out daily routines, and the occupational performance of children with ADHD ( Wennberg et al, 2018 ; Wennberg et al, 2021 ). Timing skills are related to delay aversion and to impulsivity so that time-related trainings may reduce impulsive behaviors in children as well ( Blume et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%